John and Elaine at a Press Conference - unknown:::Creator::::::::::::
John and Elaine Steinbeck sit at a press conference or meeting with writers at Collegium Maius (established 1400, 'Great College,' originally Akademia Krakowska), the historical seat of Jagiellonian University, also known as the University of Kraków in Poland.